Potential of Nisin and Newly Discovered Bacteriocins as Preservatives for Pasteurised Milk - Getrude Okiko; Ivan Sugrue; Fredrick O. Ogutu; Paul Ross (Turkish Journal of Agriculture: Food Science and Technology)
Spoilage of pasteurized milk is mainly caused by the presence of organisms that either survive pasteurization (psychrotolerant spore-formers) or re-contaminate milk in the processing environment (post-pasteurisation contaminants).  Pasteurization of bovine milk by heat treating at 72°C for 15-30 seconds ensures milk quality without impairing its organoleptic and nutritional status and extends shelf life to 12-14 days at refrigeration temperatures. Nisin A is a class I bacteriocin known to inhibit gram positive bacteria and approved by the European Food and Safety Authority as a food preservative. It is commercially available as Nisaplin®, which contains a concentration of 2.5% w/w of nisin. This study examined the effect of Nisaplin® at different concentrations on spoilage of refrigerated commercial whole pasteurized milk over a period of 59 days. At a high concentration of 4 mgml-1, Nisaplin® reduced the total bacterial count below the limit of detection in the milk, and inhibition was visible for at least 14 days at 4°C. Previously isolated milk spoilage bacteria were identified using 16s rRNA gene sequencing and utilised as target indicators for bacteriocin production. Lactobacillus delbrueckii ssp. bulgaricus LMG6901, Microbacterium lacticum, and Pseudomonas aeruginosa were utilised as indicator strains in a screen of milk spoilage organisms for bacteriocin production. This resulted in identifying the putative bacteriocin producer Carnobacterium divergens, a lactic acid bacterium active against L. bulgaricus. The study concludes that Nisaplin® is effective in the reduction of microbial load and its effectiveness could be increased when combined with other preservative methods thus forming an extra hurdle in the milk.